2014
DOI: 10.1007/s00253-014-6074-z
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and diversity of soil petroleum hydrocarbon-degrading microbial communities in oil exploring areas

Abstract: Alkanes and polycyclic aromatic hydrocarbons (PAHs) are the commonly detected petroleum hydrocarbon contaminants in soils in oil exploring areas. Hydrocarbon-degrading genes are useful biomarks for estimation of the bioremediation potential of contaminated sites. However, the links between environmental factors and the distribution of alkane and PAH metabolic genes still remain largely unclear. The present study investigated the abundances and diversities of soil n-alkane and PAH-degrading bacterial communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 52 publications
0
36
0
1
Order By: Relevance
“…Two phylotypes were closely related to the homologs of the alkB-geo1 (22 out of 43 clones) and alkB-geo6 genes (5 out of 43 clones) (Table S2). The third phylotype (16 clones) exhibited only 84% similarity to the alkB genes of cultured bacteria and 98% similarity to the alkB genes revealed in the microbial community of formation water from production wells at the onshore Potiguar Basin (Northeast, Brazil) (Verde et al, 2013) and of oil exploring area located in the Xinjiang Uygur Autonomous Region (Northwest, China) (Yang et al, 2015). The third phylotype probably belongs to a presently unknown microorganism inhabiting oilfields.…”
Section: Resultsmentioning
confidence: 99%
“…Two phylotypes were closely related to the homologs of the alkB-geo1 (22 out of 43 clones) and alkB-geo6 genes (5 out of 43 clones) (Table S2). The third phylotype (16 clones) exhibited only 84% similarity to the alkB genes of cultured bacteria and 98% similarity to the alkB genes revealed in the microbial community of formation water from production wells at the onshore Potiguar Basin (Northeast, Brazil) (Verde et al, 2013) and of oil exploring area located in the Xinjiang Uygur Autonomous Region (Northwest, China) (Yang et al, 2015). The third phylotype probably belongs to a presently unknown microorganism inhabiting oilfields.…”
Section: Resultsmentioning
confidence: 99%
“…These variations could be due to temporal (date of sample collection) and/or spatial (location of the sample collection) factors. Many biotic and abiotic factors are known to influence the abundance and diversity of microbial populations [29][30][31]. Hence, it is tempting to propose that samples, which revealed higher gene copy numbers might have higher level of contamination with PAH or naphthalene (in case of the nahA gene) or higher sulfate concentration (in case of the apsA gene).…”
Section: Discussionmentioning
confidence: 99%
“…These numbers were detected in the highly contaminated samples. Recently, Yang et al [29] targeted alkB and nah genes to investigate the abundance and diversity of n-alkane and PAH-degrading bacterial communities in soil from oil exploration areas. They found spatial variation in the distribution of alkane and PAH catabolic genes dependent on environmental variables.…”
Section: Discussionmentioning
confidence: 99%
“…In all our study of soils/sediments, the copy number of alkB genes was less than that reported for the Daqing Oilfield soils, which reached up to 9·37 × 10 7 copies per gram of dry soil (Yang et al . ). However, our soil/sediment alkB gene copies were greater than that in oil‐contaminated sediments from the Timor Sea, Australia which ranged 1·1 × 10 5 to 2·9 × 10 5 copies per gram of dry sediment (Wasmund et al .…”
Section: Discussionmentioning
confidence: 97%
“…Previously, crucial hydroxylase genes for PH degradation have been used as biomarkers to characterize the bioremediation capacity of indigenous communities (Yang et al . ; Liu et al . ).…”
Section: Introductionmentioning
confidence: 99%